Biofuels Analysis Based on the THDI Indicator of Sustainability - Lucia, Umberto; Grisolia, Giulia (Frontiers in Energy Research, 2021)
Energy resources, and their management, represent an open problem of our present days. An increasing interest in the analysis of the limits of fossil fuels use, and their availability, is growing in order to find solutions to the undesired impact of some anthropic activities to the environment. So, nowadays, a shift to renewable energy resources has become a fundamental requirement. In this context, biofuels from micro-organisms can represent a response to the requirement of reducing the environmental impact, but also to generate new jobs. In this paper, the analysis of the biofuels from micro-organisms is developed by introducing the Thermodynamic Human Development Index ($THDI$). In particular, we show how its performance can be improved by using the third generation biofuels in the road transport sector, and how it increases by exploiting biofuels derived from mutualistic species of some micro-organisms. The result consists in the fundamental role of the mutualistic behaviour of these species in order to increase the overall sustainability.